Chronic orbital inflammation associated to hydroxyapatite implants in anophthalmic sockets - Galindo-Ferreiro, Alicia; Elkhamary, Sahar M.; Maktabi, Azza; Galvez-Ruiz, Alberto; Schellini, Silvana Artioli [UNESP] (Karger Publishers, 2017)
Purpose: We report 6 patients who received a hydroxyapatite (HA) orbital implant in the socket and developed chronic orbital inflammation unresponsive to conventional medical therapy. Case Reports: We assisted 6 cases (4 males, 2 females) who received an HA orbital implant in the socket between 2015 and 2016 at King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia, and developed chronic orbital inflammation with chronic discharge, redness, and pain (onset from weeks to over 2 decades after surgery). Computed tomography evaluation indicated inflammation in the orbital tissues, and histological examination showed a foreign body granulomatous reaction mainly localized around and blanching the HA implant. The condition was unresponsive to usual medical treatment and was resolved immediately after implant removal. Conclusions: Chronic inflammation can occur decades after placement of an HA implant in the orbit and can be successfully treated with implant removal.
Keywords: Anophthalmic cavity; Chronic inflammatory reaction; Hydroxyapatite; Integrated implant